Enhancing Students’ Narrative Writing Skills through Dictogloss: Evidence from a Vocational High School Context - Kali, Marius Randan; Widyantoro, Agus; Yulia, Yuyun; Putro, Nur Hidayanto Pancoro Setyo; Purnawan, Ari (JOLLT Journal of Languages and Language Teaching, 2025)
Students’ English narrative-writing skills remain weak, yet writing competence is essential in today’s global context. This study investigated the effectiveness of the Dictogloss technique for improving students’ narrative writing through a mixed-method classroom action research design involving eleventh-grade students at SMK N 1 Tanjung Selor. Data were gathered from observations, students’ worksheets, and writing tests, and analyzed using direct observation notes, self-assessment, and an analytical writing rubric. Findings revealed consistent gains across the five key aspects of writing—content, organization, vocabulary, grammar, and mechanics. From the pre-test to Cycle 1 and Cycle 2, students’ average scores steadily increased, and by the second cycle 34 students (91.2 %) surpassed the passing mark of 75, demonstrating a substantial improvement in overall writing performance. These results confirm the strong positive impact of the Dictogloss method on students’ narrative-writing ability. Pedagogically, teachers are encouraged to integrate Dictogloss as a regular classroom practice by providing structured note-taking activities, guiding pair or group reconstruction of texts, and offering focused feedback on content development, text structure, and precise vocabulary use. Such targeted strategies help students strengthen listening, collaborative, and writing skills simultaneously, ensuring more meaningful engagement and measurable progress in narrative writing. Overall, the research underscores Dictogloss as an integrative method that enhances not only writing accuracy but also collaboration and higher-order thinking skills highly relevant for vocational students preparing for the demands of a global workforce. The implication of the study is that students are encouraged to actively engage in the Dictogloss activities, as these activities help improve writing by developing listening, note-taking, and collaborative skills. It is important to focus on the text's content, structure, and vocabulary when working in pairs, as this will enhance their writing skills.